HUBUNGAN FAKTOR LINGKUNGAN DAN PENGETAHUAN DENGAN PENGGUNAAN MAKANAN CEPAT SAJI SEBAGAI SUMBANGAN MATERI KULIAH BIOLOGI MEDIK DI STIK SITI KHADIJAH PALEMBANG TAHUN 2017 - Yunilda Rosa (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2018)
The research with the title of the relationship between environmental factors and knowledge with the use of fast food as a contribution to the Medical Biology lecture material at STIK Siti Khadijah Palembang in 2017 has been carried out. This study aims to analyze the relationship between environmental factors and knowledge with fast food use among students of STIK Siti Khadijah Palembang in 2017. This research is a descriptive research with correlation. The approach used is cross sectional. The population of this study was students of the STIK Siti Khadijah Palembang Study Program. To obtain respondent information, use a data collection tool, namely a questionnaire. Primary data is obtained through direct observation, while secondary data is obtained through data taken in the academic section of STIK Siti Khadijah Palembang. Data is processed and analyzed with technical quantitative analysis. Univariate analysis serves to describe the characteristics of each research variable. Bivariate analysis functions to see the relationship between the dependent variable and the independent variable. The results showed that: 1. The frequency distribution of fast food  users has a better value, which is 49 people (58.3%) than students who are not good at using fast food  users, namely 35 people (41.7%), knowledge frequency distribution good has more value, which is 70 people (83.3%) than students who have poor knowledge, as many as 14 people (16.7%), the frequency distribution of environmental factors does not move more, which is 48 people (57.1 %) than 36 students who use move (42.9%). 2. There is a relationship between knowledge with fast food users among STIK students in Health Siti Khadijah Palembang 2017 with a value of ? = 0.013. 3. There is no relationship between environmental factors and fast food  use among STIK (Ners Study Program) students in Siti Khadijah Palembang 2017 with a value of ? = 1,000.Keywords: environmental factors, knowledge, fast food and STIK Siti Khadijah Palembang